2007
DOI: 10.1159/000111539
|View full text |Cite
|
Sign up to set email alerts
|

Serum BDNF Levels in Suicide Attempters Related to Psychosocial Stressors: A Comparative Study with Depression

Abstract: Although many studies have examined the neurobiological aspects of suicide, the molecular mechanisms and pathophysiologic mechanisms associated with suicide remain unclear. In this study, it is aimed to investigate whether there is a difference in serum brain-derived neurotrophic factor (BDNF) levels among suicide attempters without a major psychiatric disorder, compared to major depressive disorder patients and healthy subjects. It was undertaken with the hypothesis that suicide per se lowers serum BDNF level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 59 publications
3
54
1
3
Order By: Relevance
“…Like Dwivedi et al [6,7] , Karege et al [8] also concluded that BDNF may play a role in the pathophysiology of suicidal behaviour. Most recently, serum levels of BDNF were found to be significantly lower among depressed patients who had recently attempted suicide compared with non-suicidal depressed patients and healthy controls [9][10][11] . Low serum BDNF levels have also been found to be associated with vulnerability to traumatic life events in bipolar disorder [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Like Dwivedi et al [6,7] , Karege et al [8] also concluded that BDNF may play a role in the pathophysiology of suicidal behaviour. Most recently, serum levels of BDNF were found to be significantly lower among depressed patients who had recently attempted suicide compared with non-suicidal depressed patients and healthy controls [9][10][11] . Low serum BDNF levels have also been found to be associated with vulnerability to traumatic life events in bipolar disorder [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Pek çok çalışmada tedavi almayan majör depresyon hastalarının serum BDNF seviyeleri kontrol grubuna kıyasla anlamlı derecede düşük bulunmuştur [70][71][72][73] . Literatürde BDNF düzeyleri ile özkıyım davranışı arasındaki ilişkiyi araştıran çalışmalarda özkıyım girişiminde bulunan depresif hastaların bulunmayanlara ve kontrollere kıyasla düşük BDNF düzeylerine sahip oldukları saptanmıştır 74,75 . Çalışmalar düşük BDNF seviyelerinin antidepresan tedavi yada elektrokonvulsif tedavi sonrası yükseldiğini saptamaktadır [76][77][78] .…”
Section: Depresyonda öğRenme Ve Bellekunclassified
“…Deveci y cols. 26 , investigaron los niveles séricos de BDNF entre 10 intentos de suicidio sin trastornos psiquiá-tricos graves, 24 pacientes con depresión mayor y 26 sujetos sanos, y encontraron que los niveles séricos de BDNF fueron menores entre los intentos de suicidio y los pacientes deprimidos que entre los controles sanos. Lee y cols.…”
Section: Factor Neurotrófico Derivado Del Cerebro Y Conducta Suicidaunclassified